Dracocephalum moldavica L. extract ameliorates intestinal inflammation by regulating gut microbiota and repairing the intestinal barrier in 2K1C rats - Yu, Hui; Chen, Zhangjun; Chen, Huixia; Wang, Zhanli (Archives of Biological Sciences, 2023)
Paper description: The regulatory mechanisms of the Dracocephalum moldavica extract, which is used in ethnomedicine, were examined in intestinal inflammation in hypertension. 16S ribosomal RNA gene sequencing, ELISA and RT-qPCR were performed to identify the effects of the extract in two-kidney one clip (2K1C) rats. The extract attenuated gut microbiota dysbiosis, increased short-chain fatty acids (SCFAs) levels, repaired the intestinal barrier, reduced the release of oxidative stress biomarkers and inflammatory factors, and suppressed the expression of toll-like receptor (TLR)4 and NF-κB mRNAs. The results contribute to our understanding of the regulatory mechanisms of moldavica L. in intestinal inflammation in hypertension. Abstract: When used in ethnomedicine, Dracocephalum moldavica L. (DML) and its bioactive extract protect against several diseases caused by inflammation and oxidative stress. However, the effect of DML on intestinal inflammation in hypertension has not been thoroughly investigated. This study focused on the effects of DML extract on intestinal inflammation in two-kidney, one clip (2K1C) rats. Male Wistar rats were divided into three groups with daily intragastric administration of either saline (control group and model group) or DML extract (treatment group, 50 mg/kg per day) for 4 weeks. In the model and treatment groups, 2K1C hypertension was induced by clipping the left renal artery. The profiles of stool microbiota, the levels of short-chain fatty acids (SCFAs), the integrity of the gut barrier, oxidative stress biomarkers and inflammatory factors were analyzed in rats supplemented with or without DML extract. This study revealed the alleviation of high blood pressure in 2K1C rats treated with DML extract. The DML extract attenuated gut microbiota dysbiosis in the 2K1C rats by increasing the abundance of the genus Lactobacillus and by decreasing the abundance of Papillibacter, Desulfovibrio and Anaerobiospirillum genera. Treatment with the DML extract increased the levels of SCFAs and repaired the intestinal barrier, it reduced the release of oxidative stress biomarkers and inflammatory factors and suppressed the expression of TLR4 and NF-κB mRNAs. We conclude that the DML extract may alleviate intestinal inflammation by adjusting the profile of gut microbiota and enhancing the intestinal barrier.